(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
This study aimed to evaluate the germination behavior of two morphotypes of P. cattleyanum submitted to storage and pre-germinative treatments. The experiment was designed in a factorial scheme 2 x 3 x 3 (morphotypes x storage periods x pre-germinative treatments) completely randomized, using for each treatment 5 replicates with 30 seeds. The seeds were stored in semipermeable packages in a cold chamber at 5 ± 2 ºC, for 14, 45 and 90 days. After each storage period, the seeds were submitted to treatments to overcome dormancy: immersion in water at 80 ºC kept in imbibition for 24 and 48 hours and control, without any treatment. The seeds were arranged under moistened substrate in transparent plastic boxes and allocated in a germination chamber at 25 ºC and photoperiod of 8 h for evaluation of germination percentage (G), germination speed index (GSI) and mean germination time (MGT). The red morphotype seeds showed higher germination percentages than the yellow morphotype and did not have a reduction in these values after 90 days of storage. MGT for yellow morphotype was lower in all pre-germination treatments. The GSI had better results at 45 days in the control treatments and 24 h in immersion in water and 90 days for the three pre-germinative treatments. The red morphotype does not require pre-germinative treatments, while the yellow morphotype presents better germination when the seeds are stored for 45 days and immersed in water at 80 ºC for 48 h.